(untitled) (Physical Education, Health and Social Sciences, 2025)
Domestic violence is a serious social problem that extends beyond the private sphere and significantly affects the wider community. Its consequences are not limited to the victims alone, but also affect the security of the neighborhood, social cohesion and the feeling of security of residents. This study explores the impact of domestic violence on neighborhood dynamics by analyzing the social and behavioral effects of domestic violence within neighborhoods. A quantitative research design was used to examine the relationship between domestic violence and neighborhood-related outcomes. Data were collected through a structured questionnaire using a Likert scale format to capture respondents’ perceptions and experiences. Statistical analyzes were conducted using the Statistical Package for the Social Sciences (SPSS), which includes descriptive and inferential methods to examine the association between domestic violence and neighborhood context. The results show that domestic violence negatively impacts neighborhood safety, social relationships, and overall community harmony. The increase in domestic violence incidents is associated with increased fear, decreased trust among residents, and weakened social interactions within neighborhoods. These results highlight that domestic violence is not a purely individual problem, but is an important factor influencing societal well-being. This study contributes to the literature by providing empirical evidence on the effects of domestic violence at the community level. The findings provide important implications for policymakers, law enforcement, and social service providers in developing effective prevention and intervention strategies at the community level. Statistical analysis using Pearson’s correlation was performed to examine the relationship between domestic violence and neighborhood conditions.